DESAIN BIS AIR RAMAH LINGKUNGAN SEBAGAI SARANA TRANSPORTASI ALTERNATIF DI PROVINSI DKI JAKARTA - Bambang Sudjasta; Purwo Joko Suranto (Bina Teknika, 2017)
Flood Canal was built to reduce the impact of flood during the rainy season that is river catching / times that passes in The Special Areas of The Capital of Jakarta and can accommodate the flood from Depok and Bogor. The city government is also building a mass transportation mode in Jakarta that integrates railway lines, light rail transit, roads, busway and subway networks targeted for completion in 2017 and will be integrated with the outer ring train, but if the floods are partially paralyzed. For this reason, it is necessary to empower the Flood Canal function as an alternative transportation infrastructure that is environmentally friendly water bus with a capacity of 30 passengers that can operate even in flood condition. A number of preliminary studies of water buses of earlier models and concepts have been conducted to obtain a suitable and feasible prototype to operate in the flow of West and East Canal Floods. To obtain a good water bus size calculation based on comparison ratio, general arrangement design, hull form design with CAD, hydrostatic calculation, engine power estimate and determination of required energy, stability calculation. The goal is as an environmentally friendly alternative transportation mode, with the advantage of being able to operate even in flood situations. It is expected to change the customs of the community for the canal to be the front of the house instead of the back of the house.